2017
DOI: 10.3390/su9112150
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Soil Management in Ski Areas: Threats and Challenges

Abstract: Abstract:The skiing industry often represent the main contribution to mountain regions' economy, by providing several economic benefits and the improvement of services and infrastructure. Ski resorts also play a crucial role as an impacting factor, causing severe changes on Alpine landscape and ecosystems. In particular ski runs construction and operation have considerable impacts on alpine soils, influencing their chemical and physical properties which affecting the establishment and development of plant comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Construction and its related infrastructural demands, especially at high elevation, can degenerate the soil ecosystem to the early stages of primary succession (parent materials outcrop) if pre-existing soil horizons are not effectively managed 21 . An important factor in avoiding excessive depletion of the ecosystem and securing the success of the restoration is the duration of the construction period coupled with appropriate topsoil management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Construction and its related infrastructural demands, especially at high elevation, can degenerate the soil ecosystem to the early stages of primary succession (parent materials outcrop) if pre-existing soil horizons are not effectively managed 21 . An important factor in avoiding excessive depletion of the ecosystem and securing the success of the restoration is the duration of the construction period coupled with appropriate topsoil management.…”
Section: Discussionmentioning
confidence: 99%
“…During the snow free period, cutting or grazing of vegetation is the most widely recommended management technique 20,21 , with the exclusion of the highest elevations where grazing could accelerate erosion and reduce the recovery rate. The level of initial disturbance, combined with restoration techniques and the chosen ski run management, can greatly influence the time needed for disturbed mountain slopes to recover and self-sustain 11,19 .…”
mentioning
confidence: 99%
“…Other significant factors increasing soil erosion risk are forest fires, which destroy the vegetation cover and can alter the soil's physical properties (Thomas et al 1999;Johansen et al 2001;Pardini et al 2004;Hyde et al 2007;Cannon et al 2010). In addition, recreation activities and associated infrastructures, such as hiking trails (Selkimäki and Mola-Yudego 2010), ski tracks (Pintaldi et al 2017) as well as grazing on forest pastures (Strunk 2003) can contribute to soil erosion on forest lands. Erosion processes are not always due to human activities but can also be significant in untreated forest, especially on steep slopes receiving intensive rainfall (Hartanto et al 2003;Morgan 2005).…”
Section: Erosion Risk In Forest Landsmentioning
confidence: 99%
“…Multiple studies have demonstrated the sensitivity of these habitats (Ruiz et al, 2009;Gilardelli et al, 2013). The main reasons for the vulnerability of this vegetation type are increased human impact through infrastructural development (Pintaldi et al, 2017) and high levels of grazing (Firm et al, 2009). Moreover, patches of alpine and subalpine habitats are usually small and fragmented.…”
Section: Levels Of Hoverfly Dark Diversity Across Vegetation Typesmentioning
confidence: 99%